Factors that Influenced University ABC Social Media Engagement Result: A Study Case among University ABC - Nursuhada JEKRY; Nurhidayah HASHIM; Mohd Yusof MUSTAFFAR (Communications of International Proceedings, 2021)
Nowadays, social media became one of the most crucial components of marketing and engagement plan almost in every field including education institutes. Hansson et al., (2013) stated that the rise of advance technologies and communicative platforms such as social media has allowed the users to express and interact in a new way. In addition, social media has incredible ability as it able to reach targeted populations effectively and efficiently especially in this advancement of technologies and higher competitive world. The objective of this study is to investigate the factors that may influence University ABC social media engagement result. Quantitative analysis method has been used to collect the data by giving out the questionnaires that related to the study to the students.  Several methods on how to improve social media engagement has been identified.
Keywords: Social media; University; Information; Social media engagement